2013
DOI: 10.3892/ol.2013.1310
|View full text |Cite
|
Sign up to set email alerts
|

Liposarcoma of the retropharyngeal space with rapidly worsening dyspnea: A case report and review of the literature

Abstract: Liposarcomas represent a significant proportion of soft-tissue sarcomas. However, their occurrence in the head and neck is infrequent and they are exceedingly rare in the retropharyngeal space. The present study reports the case of a 58-year-old patient with retropharyngeal liposarcoma. Uniquely, the patient presented with rapidly worsening dyspnea. The diagnosis of liposarcoma was established following retropharyngeal tumor excision, although biopsies were performed twice. Adjuvant radiotherapy was refused by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…6 Guo et al also reported a similar case with extensions from the level of the hyoid bone to the superior margin of the mediastinum, where the mass displaced trachea and larynx anteriorly and carotid arteries laterally. 7 In his report just like our case, FNAC showed features that suggested of lipoma, but after excision histopathology diagnosed it as well-differentiated liposarcoma. Azeem et al reported a similar case in the oropharynx but was extending into the oral cavity with the same clinical features and extensions.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…6 Guo et al also reported a similar case with extensions from the level of the hyoid bone to the superior margin of the mediastinum, where the mass displaced trachea and larynx anteriorly and carotid arteries laterally. 7 In his report just like our case, FNAC showed features that suggested of lipoma, but after excision histopathology diagnosed it as well-differentiated liposarcoma. Azeem et al reported a similar case in the oropharynx but was extending into the oral cavity with the same clinical features and extensions.…”
Section: Discussionsupporting
confidence: 56%
“…JG et al in his study mentioned that under microscopy, the lesion had components of mature adipocytes and lipoblasts with nuclear atypia. 7 Azeem et al in his case report revealed a well-encapsulated tumor consisting predominantly of myxoid stroma with few mature fat cells, lipoblasts and floret cells suggesting myxoid liposarcoma. 8 In our case, complete excision of the tumor was done through transcervical approach.…”
Section: Discussionmentioning
confidence: 94%
“…Myxoid LS occurs predominantly in the extremities of young adults and has a disproportionately high tendency to metastasize to unusual soft tissue locations, before giving pulmonary metastasis or disseminated spread. Some authors have described cases of myxoid LS in the retropharyngeal space [ 9 ], in the right inguinal region presenting as painless inguinal mass [ 10 ], in the breast [ 11 ], and in the spermatic cord manifesting as painless scrotal or inguinal mass [ 12 ] and a primary localization in the pericardium [ 13 ]. Other sites of metastasis may be bones, thyroid gland [ 14 ], neck, small bowel [ 15 ], pericardium, and heart and in very rare cases myxoid LS may metastasize into the pancreas [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding of a thick fibrous septum (>2 mm) on gadolinium-enhanced magnetic resonance images can accurately differentiate WDLS from benign lipoma [9] . However, the appearance of a benign lipoma may be more complex than that of a WDLS, in which case the difference cannot be distinguished radiologically [10] . Imaging studies in our case showed that the fibrous septum of the tumor was dense at the level of the larynx ( Fig.…”
Section: Discussionmentioning
confidence: 99%